(3cTa GdXdGe Yf hLhg TQGFY GdESdGes - (3eMSf Hf eQJVi Hf bGSe, J (B1238 (3g`s ((3eMeO QVG Hf eMeO GdMSfGhjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe Ydi NjQ Ndbg eMeO(B... (3CeG HYO agPG GdeLdO GdKGfj ef eLdOGJ cTa GdXdGes
(3BNQgG (B:s
(3jfJgj aj cJGH GdUdGI, YfO bhdg(B: (3hCeG GdNQhL bHd GdaLQ abO Mci GdELeGY ZjQ hGMO Ydi LhGRg(B. (3gPG JeGe GdeLdO GdKGdK ef eLdOGJ cJGH UdGI cTa GdXe Yf TQGFY GdESdGe(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B22s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B22s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis